The impact of image resolution on diagnostic accuracy using fractal dimension in identifying diabetic retinopathy, glaucoma, and age‑related macular degeneration - Che Azemin, Mohd Zulfaezal; Mohd Tamrin, Mohd Izzuddin; Yusof @ Alias, Firdaus; Salam, Adzura (Springer Nature, 2024)
Key messages What is known: What is new: Fractal dimension (FD) analysis is associated with quantifying the complexity of retinal vasculature, an essential aspect in the assessment of ocular diseases. High-resolution fundus imaging aids in detailed visualization but its impact on diagnostic precision has been unclear. FD analysis at 2048 × 2048 pixels resolution enhances the differentiation between healthy and pathological retinal The highest resolution analyzed offers significant improvement in diagnostic accuracy for diseases such as diabetic retinopathy, glaucoma, and age-related macular degeneration. This study confirms that image resolution is crucial for accurate FD analysis, correlating directly with improved states. diagnostic outcomes.